GENE-35. THE ORIGIN OF HUMAN GLIOBLASTOMA: FIREWORK PATTERN GLIOBLASTOMA GENESIS FROM SUBVENTRICULAR ZONE - Kang, Seok-Gu (Neuro Oncol, 2017)
Glioblastoma (GBM) is an incurable brain tumor, with a median overall survival of 15 months. Identifying the cell of origin that harbors mutations driving GBM could provide a fundamental basis for understanding disease developing novel treatments. Given that the accumulation of somatic mutations is implicated in gliomagenesis, studies have suggested that neural stem cells (NSCs), with their self-renewal and proliferative capacities, in the subventricular zone (SVZ) of the adult human brain may be the cells from which GBM originates. However, there is a lack of direct genetic evidence thereof in human GBM patients. Here, we describe direct molecular genetic evidence from patient brain tissue and genome edited mouse models that show astrocyte-like NSCs in the SVZ to be the cell of origin that harbors the driver mutations of human GBM. First, we performed deep sequencing of triple-matched tissues, consisting of i) radiologically and pathologically normal SVZs away from the tumor mass, ii) the tumor, and iii) normal cortical tissue (or blood), from 17 patients with primary GBM (isocitrate dehydrogenase-wild type) or other types of brain tumors. In doing so, we found that normal SVZ tissue away from the tumor in 46.2% of primary GBM patients contained low-level GBM driver mutations (down to ~1% of the mutational burden; TP53, PTEN, EGFR, PDGRF or TERT variations) that were observed at high levels in their matching tumors. Moreover, via single cell sequencing and laser microdissection analysis of patient’s brain tissues and genome editing of a mouse model (CRISPR-Cas9 system), we discovered that astrocyte-like NSCs (the astrocyte ribbon area) carrying driver mutations (TP53, PTEN, EGFR) migrate from the SVZ and lead to the development of high-grade gliomas in distant brain regions through aberrant growth. Altogether, our results highlight NSCs in human SVZ as the cell of origin that harbors the driver mutations of GBM.